A new species of Plurellidae (Ascidiacea : Phlebobranchia) from Papua New Guinea - Monniot, F.; Monniot, C. (Zootaxa, 2004)
Two colonies of a new Plurellidae, Plurella colini were collected by SCUBA in the north east and south east of Papua New Guinea. Very similar to the five other species of the genus by the external shape, in balls encrusted with sand, the new species differs in the gut shape and gonad distribution.